The Effect of Capital Intensity, Financial Distress, Growth Opportunity, and Tax Incentives on Accounting Prudence with Litigation Risk As A Moderating Variable - Khaerani, Tasya; Herawaty, Vinola (Jurnal Indonesia Sosial Sains, 2024)
This research aims to determine and examine the effect of Capital Intensity, Financial Distress, Growth Opportunity, and Tax Incentives on Accounting Prudence with Litigation Risk as a Moderating Variable. This research uses secondary data collected from the Indonesia Stock Exchange (IDX), stock information from the Yahoo Finance website, and the official websites of sector-related companies. Furthermore, this study is quantitative and employs multiple linear regression analysis, with the research population comprising the Transportation and Logistics Sector and the Technology Sector for the period 2020-2022. Based on the hypothesis testing results, the study shows that the Capital Intensity variable positively affects Accounting Prudence. Additionally, financial distress has a negative effect on accounting Prudence. Meanwhile, Growth Opportunities and Tax Incentives do not affect Accounting Prudence. Furthermore, the Litigation Risk variable cannot moderate the relationship between Capital Intensity, Financial Distress, Growth Opportunity, and Tax Incentives with Accounting Prudence.